2018
DOI: 10.1021/acsomega.7b01894
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Stimulation of Neurotypic Cells Using Persistent Photoconductivity of Gallium Nitride

Abstract: The persistent photoconductivity (PPC) of the n-type Ga-polar GaN was used to stimulate PC12 cells noninvasively. Analysis of the III–V semiconductor material by atomic force microscopy, Kelvin probe force microscopy, photoconductivity, and X-ray photoelectron spectroscopy quantified bulk and surface charge, as well as chemical composition before and after exposure to UV light and cell culture media. The semiconductor surface was made photoconductive by illumination with UV light and experienced PPC, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…The work demonstrated that there is a change in intracellular calcium concentration in the presence of GaN with PPC. The reported biological assay data solidified the observation that one can noninvasively stimulate PC12 cells in vitro …”
Section: Conductivity and Photoconductivitysupporting
confidence: 64%
See 1 more Smart Citation
“…The work demonstrated that there is a change in intracellular calcium concentration in the presence of GaN with PPC. The reported biological assay data solidified the observation that one can noninvasively stimulate PC12 cells in vitro …”
Section: Conductivity and Photoconductivitysupporting
confidence: 64%
“…It is important to understand if electronic properties of materials such as PPC are the main effect driving observations in biointerface studies. Our group recently performed KPFM in conjunction with in vitro studies to map PPC‐induced stimulation of PC12 cells . A statistically significant number of KPFM results were collected with both p‐ and n‐type Ga polar GaN samples.…”
Section: Conductivity and Photoconductivitymentioning
confidence: 99%
“…3c ). This indicates that the GNR-based PPC device has very high environmental stability and can be used for various biological applications such as DNA sequencers in micro fluid devices 19 , in vivo imaging 20 , and microchip implants 21 .
Figure 3 ( a , b ) ( a ) Optical microscope image and ( b ) Schematic illustration of PPC measurement in water.
…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the PPC was also systematically investigated. The very stable GNR-based PPC device has a huge potential for the realization of ultra-low-power non-volatile memory and various biological applications such as DNA sequencers in micro fluid devices 19 , in vivo imaging 20 , and microchip implants 21 . Our results demonstrate a novel direction of GNR study for optoelectrical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown GaN to be stable in even harsh conditions, and no signicant leaching over a 2 days period. 25,33 This study, up to this point, has largely ignored the cellular mechanics and processes which might be involved in cellular stimulation while instead focusing on the material's properties (PPC, doping, chemistry, etc.). It is important to note however that both, intracellular ROS production and calcium release are important intracellular signaling molecules, which are present in various organelles in the cell, and oen have either self-amplifying or deteriorative relationships depending on not only the organelle function, but also the metabolic state of the cell.…”
Section: Changes In [Ca 2+ ] I and Ros Productionmentioning
confidence: 99%